Average Error: 0.0 → 0.0
Time: 11.4s
Precision: 64
\[\left({2}^{x} - x\right) + {2}^{x}\]
\[\left({2}^{x} - x\right) + {2}^{x}\]
\left({2}^{x} - x\right) + {2}^{x}
\left({2}^{x} - x\right) + {2}^{x}
double f(double x) {
        double r21447205 = 2.0;
        double r21447206 = x;
        double r21447207 = pow(r21447205, r21447206);
        double r21447208 = r21447207 - r21447206;
        double r21447209 = r21447208 + r21447207;
        return r21447209;
}

double f(double x) {
        double r21447210 = 2.0;
        double r21447211 = x;
        double r21447212 = pow(r21447210, r21447211);
        double r21447213 = r21447212 - r21447211;
        double r21447214 = r21447213 + r21447212;
        return r21447214;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[\left({2}^{x} - x\right) + {2}^{x}\]
  2. Final simplification0.0

    \[\leadsto \left({2}^{x} - x\right) + {2}^{x}\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "pow(2,x)-x+pow(2,x)"
  (+ (- (pow 2.0 x) x) (pow 2.0 x)))